VARIABEL-VARIABEL RASIO KEUANGAN YANG MEMPENGARUHI HARGA SAHAM EMITEN YANG TERDAPAT PADA INDEKS SRI KEHATI DI BURSA EFEK INDONESIA - Santo Santo; Agus Rahman Alamsyah; Theresia Pradiani (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Capital market is an indicator and support of a state’s economic development. The phenomenon of significant increase of number data of investors in Indonesia capital market for the year ended August 31, 2021 amount to 2.219.721 investors with total of 6.100.525 investors. The activity objective in capital market through buying financial instrument such as stocks, is to have capital gain and dividend. The objective of this study is to analyze fundamental factors of company’s stock listed in SRI-KeHati Index of Indonesia Stock Exchange during 2016-2020. Fundamental factors represented by liquidity, solvency and profitability ratio. This study uses explanatory research with quantitative approach. The test conducted in this study, uses hypothetical testing method with classical assumptions test and multiple linear regression analysis. The results indicate that 1) Liquidity ratio proxy by current ratio(CR) has a positive significant impact on the stock prices. 2} Solvency ratio proxy by debt to equity ratio(DER) has positive and unsignificant impact on the stock prices. 3} Profitability ratio proxy by return on assets ratio(ROA) has a negative and unsignificant impact on the stock prices.